Exploring Students’ Preferences Between Gamified Quiz Platform vs Traditional Text-Based Quizzes in An Indonesian EFL Context: A Qualitative Study at SMA Widyagama Malang - Vera Marta Sabila; Putu Dian Danayanti Degeng (Jurnal Ragam Pengabdian, 2026)
This study investigates the preferences and emotional responses of Indonesian secondary school students toward gamified quiz platforms versus traditional text-based quizzes in an EFL classroom. Despite the growing adoption of gamified assessment tools, qualitative research exploring secondary students' psychological experiences with these formats remains limited. Grounded in Self-Determination Theory (SDT), this study examined how each quiz format fulfills or hinders students' basic psychological needs for autonomy, competence, and relatedness. A qualitative approach was employed with five purposively selected eleventh-grade students from SMA Widyagama Malang. Over eight weeks, participants engaged with both gamified platforms (Blooket and Zep Quiz) and conventional text-based quizzes. Data were collected through semi-structured interviews based on the Basic Psychological Need Satisfaction and Frustration Scale (BPNSFS) and analyzed using thematic analysis. The findings reveal that gamified quizzes enhanced enjoyment, reduced stress, and strengthened peer interaction, while supporting students' sense of autonomy and relatedness. Text-based quizzes, though less emotionally engaging, were perceived as more cognitively demanding and academically rigorous. All participants preferred gamified quizzes while acknowledging the value of traditional formats. These findings suggest that integrating both assessment types best supports students' emotional engagement and cognitive development in EFL classrooms.